Integrating ayurvedic eye care into primary health practice: an exploratory study on the combined effect of pratimarsha nasya, avagundana, and aschyotana in meibomian gland dysfunction - P, Sreelekha; Naranappa Salethoor, Sushma; K, Shanti (Frontiers in Medicine, 2026)
BackgroundMeibomian Gland Dysfunction (MGD) has become increasingly common in community practice, often presenting as dryness, irritation, and ocular fatigue. Factors such as prolonged screen exposure, environmental irritants, and advancing age contribute to its growing burden in primary health settings. Conventional management usually focuses on symptom relief, leaving a need for safer, sustainable options that can be applied easily in routine care. Ayurvedic eye therapies, known for their gentle yet restorative effects, may offer such an alternative.MethodsA single-arm, open-label clinical study was conducted on 30 patients with clinically diagnosed Meibomian Gland Dysfunction (MGD). The treatment protocol consisted of daily nasal oil instillation (pratimarsha nasya) using Anu oil for 30 days, along with medicated eye drops (aschyotana) prepared from Moringa oleifera leaves and localized warm ocular fomentation (avagundana) using a herbal bolus immersed in a Triphala-based decoction for the first 15 days. Clinical outcomes were assessed using both subjective and objective parameters, including the Ocular Surface Disease Index (OSDI), Tear Film Break-Up Time (TBUT), Schirmer’s Test I, fluorescein staining, and meibomian gland expressibility. Assessments were performed at baseline, immediately after treatment, and during follow-up visits. Data were analyzed using the Friedman test and Wilcoxon Signed-Rank test.ResultsPatients showed marked improvement in all clinical parameters. OSDI, TBUT, and Schirmer’s scores improved significantly (p < 0.001). Fluorescein staining was reduced to nil after treatment and remained stable during follow-ups, while meibomian gland expressibility improved consistently, reflecting better tear film stability and glandular function. No side effects or adverse reactions were reported.ConclusionThis exploratory study suggests that a simple Ayurvedic care regimen may be associated with improvement in symptoms and ocular surface parameters in individuals with Meibomian Gland Dysfunction. Given its non-invasive nature, ease of administration, and suitability for low-resource settings, this approach may have potential relevance as a supportive strategy within primary eye care. However, these findings are preliminary, and further controlled studies are required to confirm effectiveness and define its role in community-level preventive and promotive eye health.Limitations of the studyThis was a single-arm exploratory study with a small sample size and limited follow-up. Consequently, the findings are preliminary and require confirmation in controlled trials.